2017
DOI: 10.1007/s41403-017-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Thermal Properties and Electrical Properties of Polylactide Doped with Nano Aluminium Oxide and Nano Cupric Oxide

Abstract: The research on polylactide has been trending over the past 10 years as it is a versatile biopolymer which finds applications in food packaging and medical industries. In this research, nano aluminium oxide and nano cupric oxide have been impregnated into polylactide matrix using sonication and the nano composite thin films were prepared using solution casting technique. The thermal characterization of the neat and doped polymer films were conducted using thermogravimetric analysis and differential scanning ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…10 that all samples show a transition peak in the temperature range of 50-60 • C (Stage 1), which is related to the glass transition of the PLA and PLA/CTAC-MMT composites. At Stage 2, we notice that neat PLA material showed an exothermic trough at temperatures of 140-160 • C which revealed a less similar trend from works by Abdul et al [66] and Tabi et al [67]. Although their range showed an earlier curve at 80 • C, the difference can be attributed to the fact that the membrane used was moist and that there was possible contamination.…”
Section: Mechanical Testingsupporting
confidence: 70%
“…10 that all samples show a transition peak in the temperature range of 50-60 • C (Stage 1), which is related to the glass transition of the PLA and PLA/CTAC-MMT composites. At Stage 2, we notice that neat PLA material showed an exothermic trough at temperatures of 140-160 • C which revealed a less similar trend from works by Abdul et al [66] and Tabi et al [67]. Although their range showed an earlier curve at 80 • C, the difference can be attributed to the fact that the membrane used was moist and that there was possible contamination.…”
Section: Mechanical Testingsupporting
confidence: 70%
“…Despite the fact that most of these studies concern the use of highly conductive nanoparticles (NP), based on carbon [37][38][39][40][41][42] or silver [43,44], attempts are being made to use less obvious fillers. Mujeeb et al [45] used a solution casting method of prepared nanocomposites based on polylactide and aluminum oxide nanoparticles. Their studies showed a 35-45% reduction in resistivity of PLA.…”
Section: Introductionmentioning
confidence: 99%
“…Research in nanocomposites of PLA with alumina is focused on the thermal and electrical properties of the composites [ 61 ], but not on 3D printing as a manufacturing process. PLA in fiber form has also been used for the preparation of composites with alumina, employing the electrospinning process [ 62 ].…”
Section: Introductionmentioning
confidence: 99%